A perspective from the European Network for Bipolar and Emotion Regulation on research and intervention for emotion dysregulation in bipolar disorder: challenges and lessons learned - Azevedo, Julieta; Dodd, Alyson; Weiner, Luisa; M’Bailara, Katia; Pinto, Ana M.; Weibel, Sébastien; Lawlor, Caroline; Koenders, Manja; Wright, Kim (Frontiers in Psychiatry, 2025)
Bipolar disorder (BD) and emotion dysregulation present substantial challenges for individuals and healthcare providers. Although pharmacological treatments remain the primary approach, psychosocial interventions show promise in addressing sub-threshold symptoms and deepening understanding of mood and emotion dysregulation mechanisms. The European Network for Bipolar Emotion Regulation (ENBER) aims to close the gap between research and clinical practice by offering practical insights for clinicians while contributing to scientific discourse on BD and emotion regulation (ER). This perspective paper identifies key questions for the field, suggesting directions for future research and highlighting promising interventions, such as Dialectical Behaviour Therapy (DBT), which have shown potential to reduce emotion dysregulation and improve personal recovery in BD. Future research should explore the flexibility and context-appropriateness of ER strategies, considering how current mood states significantly impact these dynamics. The commentary advocates for personalised treatment approaches that address individual differences in symptoms and ER capabilities, recommending innovative methodologies to better understand and apply ER in BD.Incorporating patient perspectives into research design is also a necessary focus for future research, having the potential to improve recovery and quality of life for individuals with BD.